The new Common Agricultural Policy CAP. Prices of raw materials and manufacturing - Silva J.M. (Feed manufacturing in Southern Europe: New challenges, 1997)
The author explains why and how the CAP has been reformed, specially in the cereal area. He presents as a first objective the promotion of the consumption of cereals produced in the Community. He explains the tendencies of the evolution in the prices and production of cereals for the 1996-97 period.
South European Feed Manufacturers Conference, 1996/05/09-11, Reus (Spain)